Pulse Width Modulation-A Study - Vishakha Garg (Journal of Electronic Design Engineering, 2015)
To fulfill partial power requirements, variable resistance devices such as rheostats were used to control the current entering a device (i.e., sewing machines). These devices suffered from major energy losses from heat in the resistor elements. Other device power control devices included voltage stepping autotransformers such as the Autrastat. There was a need for a low cost, efficient and compact option for providing adjustable power for electronic devices. Variable (Switching) power supplies began being used in mass by the military commercial product designers became curious when seeing the military applications of the switching power supplies. One of the early applications of Pulse Width Modulation was in the Sinclair X10, an audio amplifier in the 1960s. In 1976, Bob Mammano (Silicon General) invented the SG1524 regulating pulse width modulator integrated circuit. Pulse Width Modulation variable speed drives are increasingly applied in many new industrial applications that require superior performance. Recently, developments in power electronics and semiconductor technology have lead improvements in power electronic systems. Hence, different circuit configurations namely multilevel inverters have become popular and considerable interest by researcher are given on them. Variable voltage and frequency supply to A.C drives is invariably obtained from a three-phase voltage source inverter. A number of Pulse Width Modulation (PWM) schemes are used to obtain variable voltage and frequency supply. The most widely used PWM schemes for three-phase voltage source inverters are carrier-based sinusoidal PWM and space vector PWM (SVPWM). There is an increasing trend of using space vector PWM (SVPWM) because of their easier digital realization and better dc bus utilization.